2015
DOI: 10.1186/s13012-016-0491-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessing outcomes of enhanced chronic disease care through patient education and a value-based formulary study (ACCESS)—study protocol for a 2×2 factorial randomized trial

Abstract: BackgroundChronic diseases result in significant morbidity and costs. Although medications and lifestyle changes are effective for improving outcomes in chronic diseases, many patients do not receive these treatments, in part because of financial barriers, patient and provider-level knowledge gaps, and low patient motivation. The Assessing outcomes of enhanced chronic disease care through patient education and a value-based formulary study (ACCESS) will determine the impact of two interventions: (1) a value-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…For patients with diabetes mellitus, there is a correlation between the risk of CHD and diabetes-related risk factors such as hyperglycemia, hyperlipidemia, insulin resistance, hyperinsulinemia and other factors ( 8 ), which leads to atherosclerosis and further aggravates the development of the disease ( 9 ). Previous studies have confirmed that the incidence of cardiovascular events in diabetic patients complicated with CHD is related to factors in the patients such as age, obesity, high blood lipids profile, increased blood pressure and other items ( 10 ). However, there is still little known about the association of blood glucose abnormalities, insulin resistance or inflammatory responses of the body with T2DM and CHD.…”
Section: Discussionmentioning
confidence: 84%
“…For patients with diabetes mellitus, there is a correlation between the risk of CHD and diabetes-related risk factors such as hyperglycemia, hyperlipidemia, insulin resistance, hyperinsulinemia and other factors ( 8 ), which leads to atherosclerosis and further aggravates the development of the disease ( 9 ). Previous studies have confirmed that the incidence of cardiovascular events in diabetic patients complicated with CHD is related to factors in the patients such as age, obesity, high blood lipids profile, increased blood pressure and other items ( 10 ). However, there is still little known about the association of blood glucose abnormalities, insulin resistance or inflammatory responses of the body with T2DM and CHD.…”
Section: Discussionmentioning
confidence: 84%
“…The ACCESS trial is a pragmatic clinical trial in Alberta, Canada, which completed recruitment in August 2018 (ClinicalTrials.gov registration NCT02579655). ACCESS is a factorial (2 × 2) RCT that is evaluating the impact of providing free high-value medications and/or a tailored health education program on patient outcomes and health care costs among seniors at high risk of cardiovascular complications [30]. The free medications intervention involved elimination of patients’ 25% copayments for all medications considered high value in preventing cardiovascular disease (Additional file 1).…”
Section: Methodsmentioning
confidence: 99%
“…Participants who stated a preference for electronic communication during eligibility screening received regular emails and access to a personalized electronic platform in addition to the mailers. The details of the programme are reported elsewhere, 21 Finally, MOXIE included a facilitated relay intervention whereby patients were sent letters regarding indicated medications, which were tailored based on the information provided at baseline.…”
Section: Access Trialmentioning
confidence: 99%
“…The trial aims to evaluate the impact of two interventions targeting financial barriers and lack of knowledge, among low-income seniors with high CV risk in Alberta, Canada. 21,22 The interventions are as follows: (1) a comprehensive tailored self-management education and support (SMES) programme including facilitated relay of clinical information to participants' health-care providers; and (2) elimination of copayments for select high-value cardioprotective medications (comparing with standard care: copayments of 30% of drug costs, to a maximum of $25/medication/dispensation). We hypothesized that these interventions would result in improved medication adherence and health behaviour changes, ultimately resulting in fewer hospitalizations, CV events and deaths.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation